An Efficient Cyanide-Free Approach towards 1-(2-Pyridyl)isoquinoline-3-carbonitriles via the Reaction of 5-Phenacyl-1,2,4-triazines with 1,2-Dehydrobenzene in the Presence of Alkyl Nitrites - Kopchuk, Dmitry S.; Krinochkin, Alexey P.; Khasanov, Albert F.; Kovalev, Igor S.; Slepukhin, Pavel A.; Starnovskaya, Ekaterina S.; Mukherjee, Anindita; Rahman, Matiur; Zyryanov, Grigory V.; Majee, Adinath; Rusinov, Vladimir L.; Chupakhin, Oleg N.; Santra, Sougata (Synlett, 2018)
A cyanide-free method for the preparation of 1-(2-pyridyl)isoquinoline-3-carbonitriles (3-cyanoisoquinolines) was developed. The interaction of 5-phenacyl-3-(2-pyridyl)-1,2,4-triazines with 1,2-dehydrobenzene generated in situ from anthranilic acid and an excess of amyl nitrites afforded the target compounds in good yields. The proposed mechanism involves the in situ transformation of the 5-phenacyl group into the 5-cyano group under the action of alkyl nitrite and the following inverse demand aza-Diels–Alder reaction of thus formed 5-cyano-1,2,4-triazines with 1,2-dehydrobenzene affording the target products. The presence of the 5-phenacyl substituent is a key for the reaction, as in case of 5-styryl- or 5-phenylethynyl-3-(2-pyridyl)-1,2,4-triazines the formation of the 1,2,4-triazine ring-transformation products was observed
Keywords: 1-(2-pyridyl)isoquinoline-3-carbonitriles; cyanide-free; aryne; inverse demand aza-Diels–Alder reaction; alkyl nitrites